Palestinian Liberation in Education: Solidarities and Activism for a Free Palestine (Part 1) - Shatara, H. (Critical Education)

(untitled) (Institute for Critical Education Studies / UBC, 2026)
This special issue sheds light on the resistance and activism within educational spaces, inside and outside of classrooms and universities, for the liberation of Palestine. The issue is split into two parts, both with similar overarching themes. The first issue focuses on three themes: foundations, community activism, and hope.